2009
DOI: 10.1590/s1807-59322009000700005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Findings in Patients Examined in Cataract Detection-and-Treatment Campaigns: A Retrospective Study

Abstract: INTRODUCTION:A cataract is defined as an opacity of any portion of the lens, regardless of visual acuity. In some advanced cases of cataracts, in which good fundus visualization is not possible, an ultrasound examination provides better assessment of the posterior segment of the globe.OBJECTIVES:This study aims to evaluate the ultrasonographic records of patients with advanced cataracts who were examined during cataract campaigns.METHODS:The ultrasonographic findings obtained from 215 patients examined in cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Abnormal USG findings were observed in 78 eyes (12.5%). Commonest were retinal detachment (4%) and posterior vitreous detachment (2%) followed by poseriorstaphyloma (1.6%) and vitreous haemorrhage (0.8%).. Mendes et al (2009), who studied sonographic findings in patients with cataract and reported vitreous opacities to be the most common abnormality (12.1%). Retinal detachment the most common finding on USG is attributed to fluid in the vitreous cavity which passes through holes or tears directly in the retina (subretinal fluid) and separates the retina from the underlying pigmented retinal epithelium (Wilkinson, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal USG findings were observed in 78 eyes (12.5%). Commonest were retinal detachment (4%) and posterior vitreous detachment (2%) followed by poseriorstaphyloma (1.6%) and vitreous haemorrhage (0.8%).. Mendes et al (2009), who studied sonographic findings in patients with cataract and reported vitreous opacities to be the most common abnormality (12.1%). Retinal detachment the most common finding on USG is attributed to fluid in the vitreous cavity which passes through holes or tears directly in the retina (subretinal fluid) and separates the retina from the underlying pigmented retinal epithelium (Wilkinson, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…India is committed to the goal of elimination of avoidable blindness by 2020 (Murthy et al, 2008). Cataract has been defined as an opacity of any part of the lens (Mendes et al, 2009). Many of these cases have advanced stage cataracts which http://jmscr.igmpublication.org/home/ ISSN (e)-2347-176x ISSN (p) 2455-0450 DOI: https://dx.doi.org/10.18535/jmscr/v7i8.153 preclude the visualization of fundus before cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Ophthalmoscope and OCT are easily affected by refractive medium turbidity [ 2 ]. Although ocular B-ultrasound is not affected by refractive medium turbidity, its accuracy in diagnosing retinopathy is not high [ 1 , 3 ]. In recent years, objective visual electrophysiology technology has been widely studied by cataract experts [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Int J Med sci, 2022;2(1):32-38 ultrasonogram (brightness modulation scan) was introduced to the ophthalmic practice in 1973. (10) There was a rapid progression in the development of ultrasound machines, with high-resolution imaging can be achieved, getting the benefit of superficial place of the eye, aqueous chambers and vitreous body has a good acoustic media, with correct results (11,12,13).…”
Section: Introductionmentioning
confidence: 99%